Class III PI3K-mediated prolonged activation of autophagy plays a critical role in the transition of cardiac hypertrophy to heart failure - Yu, Peng (J Cell Mol Med, 2015)
Pathological cardiac hypertrophy often leads to heart failure. Activation of autophagy has been shown in pathological hypertrophic hearts. Autophagy is regulated positively by Class III phosphoinositide 3-kinase (PI3K). However, it is unknown whether Class III PI3K plays a role in the transition of cardiac hypertrophy to heart failure. To address this question, we employed a previously established cardiac hypertrophy model in heat shock protein 27 transgenic mice which shares common features with several types of human cardiomyopathy. Age-matched wild-type mice served as control. Firstly, a prolonged activation of autophagy, as reflected by autophagosome accumulation, increased LC3 conversion and decreased p62 protein levels, was detected in hypertrophic hearts from adaptive stage to maladaptive stage. Moreover, morphological abnormalities in myofilaments and mitochondria were presented in the areas accumulated with autophagosomes. Secondly, activation of Class III PI3K Vacuolar protein sorting 34 (Vps34), as demonstrated by upregulation of Vps34 expression, increased interaction of Vps34 with Beclin-1, and deceased Bcl-2 expression, was demonstrated in hypertrophic hearts from adaptive stage to maladaptive stage. Finally, administration with Wortmaninn, a widely used autophagy inhibitor by suppressing Class III PI3K activity, significantly decreased autophagy activity, improved morphologies of intracellular apartments, and most importantly, prevented progressive cardiac dysfunction in hypertrophic hearts. Collectively, we demonstrated that Class III PI3K plays a central role in the transition of cardiac hypertrophy to heart failure via a prolonged activation of autophagy in current study. Class III PI3K may serve as a potential target for the treatment and management of maladaptive cardiac hypertrophy.